Rapid Quantitative Point-Of-Care Diagnostic Test for Post COVID-19 Vaccination Antibody Monitoring - Moeller, Maria E.; Engsig, Frederik N.; Bade, Melanie; Fock, Jeppe; Pah, Pearlyn; Soerensen, Anna Louise; Bang, Didi; Donolato, Marco; Benfield, Thomas (Microbiology spectrum, 2022)
Serological testing is an important diagnostic support tool in the fight against COVID-19. So far, serological testing has been performed on either lateral flow assays, which perform only qualitatively and can be difficult for the individual to read, or standard laboratory assays, which are time- and resource-consuming. Point-of-care (POC) quantification of antibody responses against SARS-CoV-2 spike protein can enable decentralized monitoring of immune responses after infection or vaccination. We evaluated a novel POC microfluidic cartridge-based device (ViroTrack Sero COVID-19 Total Ab) for quantitative detection of total antibodies against SARS-CoV-2 spike trimeric spike protein compared to standard laboratory chemiluminescence (CLIA)-based tests. Antibody responses of 101 individuals were measured on capillary blood, venous whole blood, plasma, and diluted plasma samples directly on the POC. Results were available within 7 min. As the reference, plasma samples were analyzed on DiaSorin LIAISON XL CLIA analyzer using LIAISON SARS-CoV-2 IgM, LIAISON SARS-CoV-2 S1/S2 IgG, and LIAISON SARS-CoV-2 TrimericS IgG assays. The Spearman rank’s correlation coefficient between ViroTrack Sero COVID-19 Total Ab and LIAISON SARS-CoV-2 S1/S2 IgG and LIAISON SARS-CoV-2 TrimericS IgG assays was found to be 0.83 and 0.89, respectively. ViroTrack Sero COVID-19 Total Ab showed high correlation between the different matrixes. Agreement for determination of samples of >230 binding antibody units (BAU)/mL on POC and CLIA methods is estimated to be around 90%. ViroTrack Sero Covid Total Ab is a rapid and simple-to-use POC test with high sensitivity and correlation of numerical results expressed in BAU/mL compared to those of a commercial CLIA assay. IMPORTANCE Serological testing is an important diagnostic support tool in the fight against COVID-19. So far, serological testing has been performed on either lateral flow assays, which perform only qualitatively and can be difficult for the individual to read, or standard laboratory assays, which are time- and resource-consuming. The purpose of the study was to evaluate the performance of a new POC microfluidic cartridge-based device based on immunomagnetic agglutination assay that can provide an accurate numerical quantification of the total antibodies within only 7 min from a single drop of capillary blood. We demonstrated a high level of correlation between the POC and the two CLIA laboratory-based immunoassays from Diasorin, thus allowing a potentially wider use of quantitative serology tests in the COVID-19 pandemic.